THE RELATIONSHIP OF PARENT AND STUDENTS COMMUNICATION WITH CLASS IV STUDENTS CHARACTER SDN 091281 BATU IV SIANTAR - Minar Trisnawati Tobing; Catherine Mayrika Panjaitan (SENSEI RESEARCH CENTER, 2021)
This type of research is descriptive correlational. The population of this research data is the entire class IV SD Negeri 091281 Batu IV Siantar as many as 2 classes in this study using random samples (random sampling) that is 20% of the total population of 40 students. The data collection tools in this research are questionnaire, documentation, and questionnaire consists of 20 items, and each has four options (a, b, c, d). Before the questionnaire was used, it was first tested to determine the validity and reliability of the questionnaire. The test results of the requirements analysis of the normality of parent-child communication with the Character of Class IV SD Negeri 091281 Batu IV. At the significant level, that is X^2 count < X^(2 ) table (29,48<55,76) Characters of class IV SD Negeri 091281 Batu IV Siantar. That is X^(2 )counit <X^2 table (43,87<55,76). Linearity test of parent and child communication with Civics learning outcomes for students IV SD Negeri 091281 Batu IV Siantar.